Efficient isolation of lupin protein - Jayasena, Vijay; Chih, Hui Jun; Nasar-Abbas, Syed (Australian Institute of Food Science and Technology Inc., 2011)
The increasing demand for low cost and non-genetically modified vegetable proteins has pushed the food industry to explore alternate sources of protein. Lupin has been found to have similar protein content and amino acid profile to that of soy. In particular, the Australian Sweet Lupin (Lupinus angustifolius), a low alkaloid variety of lupin, is high in protein and fibre and low in fat, making it an ideal food ingredient for health and well being. Concentrated form of lupin protein with protein content of 90% was prepared by alkaline extraction at pH 9.0 followed by acidic precipitation at eight different pH levels (4.0, 4.2, 4.4, 4.5, 4.6, 4.8, 5.0 and 5.5). The range of pH employed covered the isoelectric points of major legume proteins. The results revealed that there was no significant difference in protein content and yield of lupin protein isolates precipitated at pH 4.4, 4.5, 4.6, 4.8 and 5.0. The finding indicated that instead of using pH 4.5 for lupin protein precipitation, a higher pH such as 5.0 can be used that would result in decreased acid usage, thus providing a more economical approach to protein isolate production.